Penerapan Model Pembelajaran Problem Based Learning ( PBL) Untuk Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran Kewirausahaan Kelas X AK/PM SMK MuhammadiyahDelanggu Tahun Ajaran 2015/2016 - DEWI, INTAN NOKA, Drs. Djumali, M.Pd (2016)
Class Action Research aims to improve students' learning activeness on the subjects of entrepreneurship through learning model Problem Based Learning (PBL). The research subject is class X AK / PM SMK Muhammadiyah Delanggu totaling 28 students. Data collection methods used were observation, interviews, field notes and documentation. To ensure the validity of data used triangulation techniques. Data analysis technique used consisted of data reduction, data presentation and verification of data. The results showed an increase in activity of student learning in the entrepreneurial learning through the application of learning models Problem Based Learning (PBL). It can be seen from 1) activity of students participating in performing the task of learning before action by 82.14% and after the action to be 100%. 2) Students who engage in problem solving before the action amounted to 32.14% and 71.43% after the action becomes. 3) Students who dared to ask other students or teachers before actions 17.85% and amounted to 53.57% after the action. 4) Students are trying to find the information needed to solve the problem before action by 25% and amounted to 71.43% after the action. 5) Students who carry out the corresponding command group discussions teacher before action is 57.14% and amounted to 96.43% after the action. 6) students assess her abilities and the results obtained prior to action by 17.85% and amounted to 60.71% after the action. From the research results support the hypothesis "if entrepreneurial learning through the application of learning models Problem Based Learning is done properly and appropriately, it can enhance The activity of students in entrepreneurial learning".